Seed Harvesting at Different Maturity Stages of Siliqua on Seed Quality of Rapeseed-Mustard Varieties - Talukder, AHMMR; Biswas, M; Miah, MNH; Kashem, MA; Nahar, L (Bangladesh Agronomy Journal, 2020)
A laboratory experiment with three replicates was conducted at Plant Physiology Division research laboratory of Bangladesh Agricultural Research Institute (BARI) during November, 2015 to observe the seed quality of rapeseed-mustard by harvesting at different maturity stages of siliqua. Seeds were collected from siliqua of different rapeseed-mustard varieties and harvesting was made at different maturity stages based on their external color i.e., Green, pale yellow, Golden yellow and full maturity stage of siliqua. After harvesting of siliqua as per external color seeds were dried naturally about 48 hours and were packed in polythene and stored at laboratory environment for next season uses. Under laboratory condition seeds were evaluated in terms of moisture and germination percentage, speed of germination, root and shoot length, vigor index etc. Moisture content was found significantly at elevated level in respect of mustard varieties of BARI Sarisha-14 (V2), BARI Sarisha-6 (V3) and Tori-7 (V4). The variety Tori-7 and BARI Sarisha-14 showed the highest vigor index-II & vigor index-I, respectively. Among the harvesting stages, most of the parameters showed the highest standards in seeds harvesting at full maturity of siliqua stage (H4) followed by the golden yellow siliqua stage (H3) and pale yellow siliqua stages seeds (H2).Irrespective of rapeseed-mustard varieties seed collected from golden yellow and pale yellow siliqua stages could be stored up to twelve month for next season without significant loss in terms of germination percentage and vigor followed by full maturity stages of siliqua harvested seeds (H4). Bangladesh Agron. J. 2019, 22(1): 121-130